Studies of stability in rolling sphere robot - Norul Hasanah, Ahmad Marzuki (2018)
The demand for high tech artificial intelligence continues to rise day by day. Several inventions had taken place to develop a working Rolling Sphere Robot and some of this design works perfectly with balanced weight distribution. An industrial area has potential to cause myriad damage to personnel in terms of physical injurious and cause detrimental to health. This project is about developing a stable and agile robot that perform task meant for human. The robot is expected to spin at the high velocity produced by wheels inside the spherical. The inner momentum driven by DC motors will be installed inside the sphere causing transmission of angular momentum to the outer shell. Two internal rotor will be installed inside the robot which can control the direction of the motion. This rotor is expected to be steering device to alter direction while maintaining stability. In this project, microcontroller is going to be the brain to read instruction given through wireless module while interpreting it to control movement and direction of DC Motor. The sphere motor should continuously move regardless of curvy or rough surface. The development of the Rolling Robot mechanism will be executed after making carefully planning the methodology of this project. Once this project is fabricated, the testing will be done to obtain overall project work result. The output results will be analysed with theoretical evidence and the result will be compared with previous project.